2019
DOI: 10.1029/2018jd029828
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Trends of Nocturnal Mesopause Temperature and Altitude Revealed by Na Lidar Observations Between 1990 and 2018 at Midlatitude

Abstract: The mesopause, a boundary between mesosphere and thermosphere with the coldest atmospheric temperature, is formed mainly by the combining effects of radiative cooling of CO2, and the vertical adiabatic flow in the upper atmosphere. A continuous multidecade (1990‐2018) nocturnal temperature data base of an advanced Na lidar, obtained at Fort Collins, CO (41°N, 105°W), and at Logan, UT (42°N, 112°W), provides an unprecedented opportunity to study the long‐term variations of this important atmospheric boundary. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
3
32
1
2
Order By: Relevance
“…Near the mesopause itself, where the solar cycle variations in temperature become larger than trends introduced by anthropogenic change (or other forms of global change), the picture becomes somewhat complex, as long‐term observations are difficult, and interannual variability is large. She et al () found a −2.8 ± 0.6 K/decade trend near 92 km in lidar data, significantly larger than estimated here; this is somewhat reduced in subsequent analysis by Yuan et al () that considers the seasonal and solar cycle effects, but this is for a single location, not a global average. For other observational work relevant to the mesosphere and mesopause, see the review by Laštovička (), which substantiates the uncertainties regarding this complex atmospheric region.…”
Section: Discussioncontrasting
confidence: 68%
“…Near the mesopause itself, where the solar cycle variations in temperature become larger than trends introduced by anthropogenic change (or other forms of global change), the picture becomes somewhat complex, as long‐term observations are difficult, and interannual variability is large. She et al () found a −2.8 ± 0.6 K/decade trend near 92 km in lidar data, significantly larger than estimated here; this is somewhat reduced in subsequent analysis by Yuan et al () that considers the seasonal and solar cycle effects, but this is for a single location, not a global average. For other observational work relevant to the mesosphere and mesopause, see the review by Laštovička (), which substantiates the uncertainties regarding this complex atmospheric region.…”
Section: Discussioncontrasting
confidence: 68%
“…Like the low-frequency ionospheric reflection height, the mesopause is thought to form at a constant pressure level in winter mainly due to radiative cooling, and the other in summer, controlled mostly by the adiabatic cooling. Indeed, very recently, the longterm trends on the altitude and temperature of the high (winter, HM) and low (summer, LM) mesopause, based on the same Na lidar observations without removal of Pinatubo function and with the addition of data in 2018 has been published (Yuan et al, 2019). As shown in Figure 1a, the Pinatubo response near the mesopauses after 2000 is much reduced.…”
Section: Inspection Ofmentioning
confidence: 82%
“…Indeed, very recently, the longterm trends on the altitude and temperature of the high (winter, HM) and low (summer, LM) mesopause, based on the same Na lidar observations without removal of Pinatubo function and with the addition of data in 2018 has been published (Yuan et al, 2019). Thus, it would be of interest if the long-term trend of a constant pressure level can be observed, exhibiting atmospheric shrinking directly.…”
Section: Impact To Stratospheric Ozone Change In Midlatitude Temperatmentioning
confidence: 99%
“…The solar radio flux index F10.7 (daily) and Kp index (3‐hourly) from 2002 to 2019 are used as proxies for solar extreme ultraviolet (EUV) radiation and geomagnetic activity, respectively. F10.7 flux index is commonly used as an indicator of solar activity in many middle and upper atmospheric temperature trend studies (Forbes et al, 2014; Yuan et al, 2019). The average F10.7 is calculated as normalF10.7=)(normalF10.7adj+normalF10.7ctr81/2, where F10.7 adj is 10.7 cm solar radio flux which has been adjusted to Earth orbital radius and expressed in units of 10 −22 W/m 2 /Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Kalicinsky et al (2016) also reported a cooling trend of −0.089 ± 0.055 K/year and a significant positive sensitivity to the solar activity of 4.2 ± 0.9 K per 100 sfu in the mesopause region at Wuppertal (51°N, 7°E) by analyzing the OH temperature data series from 1988 to 2015. The Na lidar observations at 41°N during 1990–2018 of Yuan et al (2019) indicated a cooling trend of 0.25 ± 0.04 K/year for the “high mesopause” (HM) and a similar 0.23 ± 0.05 K/year cooling trend for the “low mesopause” (LM), while that during 2000–2018 shows a statistically insignificant trend of −0.02 ± 0.07 and −0.1 ± 0.09 K/year for the HM and the LM, respectively. And the lidar data also demonstrated a large response to solar flux variation of 0.03 ± 0.1 K/sfu for the LM and 0.01 ± 0.007 K/sfu for the HM.…”
Section: Introductionmentioning
confidence: 99%